Persio e il suicidio di Catone. Sulle tracce di un esercizio scolastico antico (Pers. III 44-47) - Luigi Pirovano (Erga-Logoi, 2013)
In Sat. III 44-47 Persius, referring humorously to his childhood, describes the stratagem he used, as a schoolboy, to escape from reciting Cato’s final words in front of his father’s friends. Although the overall significance of the episode is clear, two important textual problems (dicere : discere; morituri Catonis : morituro Catoni) make it difficult to understand the exact nature of the school exercise to which Persius refers. The anonymous exegete of the Commentum Cornuti, on the basis of an exemplar of Persius’ Satires with the reading dicere (or discere) Catonis, proposes to interpret the exercise as a suasoria or a speech-in-character. A careful comparison with the parallel examples surviving inside the rhetorical tradition seems to confirm this interpretation and, indirectly, offers a good reason to favour the reading morituri verba Catonis discere (or, less probably, dicere); it is also tempting to see in the expression verba morituri Catonis a deliberate allusion to a traditional formula used for the «preliminary exercise» of speech-in-character.